A Framework for Fast, Autonomous, and Reliable Tool Incorporation on iCub - Mar, Tanis; Tikhanoff, Vadim; Natale, Lorenzo (Frontiers in Robotics and AI, 2018)
One of the main advantages of building robots with size and motor capabilities close to those of humans, such as iCub, lies in the fact that they can potentially take advantage of a world populated with tools and devices designed by and for humans. However, in order to be able to do proper use of the tools around them, robots need to be able to incorporate these tools, that is, to build a representation of the tool's geometry, reach and pose with respect to the robot. The present paper tackles this argument by presenting a repository which implements a series of interconnected methods that enable autonomous, fast, and reliable tool incorporation on the iCub platform.